(untitled) (International Congress on Economics, Management and Business Studies, 2026)
Modern epidemiological data indicate that the spread of human immunodeficiency virus (HIV) infection is determined not only by individual behavioral factors, but also directly influenced by socio-hygienic conditions, sanitation levels, access to healthcare services, and the effectiveness of preventive measures. According to the World Health Organization, in 2023 more than 39 million people worldwide were living with HIV, and approximately 1.3 million new cases are reported annually.